PELATIHAN DIGITALISASI LAPORAN KEUANGAN SOFTWARE ACCURATE ACCOUNTING SYSTEM SMK SWASTA GAJAH MADA MEDAN - Sidauruk, Sri Hartati; Rizkian, Muhammad Saleh; Sari, Devi Purnama (Cattleya Darmaya Fortuna, 2025)
Community service digital technology training in financial reporting innovation aims to provide an understanding of literacy in preparing software-based digital financial reports. Accurate Accounting Software is an application for financial reporting thar is easy to use quickly and accurately. Training method in the form of practical activities by completing examples of financial transaction cases that have been prepared by the Staya Terra Bhinneka University community service team. This activity was carried out in the accounting computer laboratory of Gajah Mada School on June 10 and 11 2024, 10 -12.00 PM, with 3 activity stages, First providing basic introductory material for using software, practical work on solving financial transaction case question and theoretical case discussions. The implementation of this training makes a positive contribution to the science and technology of reporting digital accounting digital financial report for Gajah Mada school students.